2009
DOI: 10.1007/s11259-009-9221-8
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 expression in response to double-stranded RNA or LPS in cultured Fetal Bovine Lung (FBL) cells

Abstract: Fetal bovine lung (FBL) cells are used in the culture of viruses which infect cattle and ISG15 plays a role in innate immunity against viral infections. However, whether the expression of ISG15 gene can be induced in FBL cells is still unknown. In this work, the expression of ISG15 in cultured FBL cells was detected after stimulated with poly I:C or LPS. Real-time PCR analyses revealed that the transcript of ISG15 can be induced by poly I:C or LPS. The increased expression of free ISG15 was confirmed via Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(21 reference statements)
0
12
0
1
Order By: Relevance
“…In our previous work it has been shown that bIRF-3 is the key factor in the induction of bISG15 in FBL cells treated with poly I:C [14] . IRF-3 commonly exists in the cytoplasm, after some stimulation by molecules such as dsRNA, then phosphorylated, dimerized and translocated to the nucleus to induce the expression of interferon stimulated genes (ISGs) [1] .…”
Section: Bhv Protein Bicp0 Inhibited the Activation Of Bisg15 Promotementioning
confidence: 93%
See 4 more Smart Citations
“…In our previous work it has been shown that bIRF-3 is the key factor in the induction of bISG15 in FBL cells treated with poly I:C [14] . IRF-3 commonly exists in the cytoplasm, after some stimulation by molecules such as dsRNA, then phosphorylated, dimerized and translocated to the nucleus to induce the expression of interferon stimulated genes (ISGs) [1] .…”
Section: Bhv Protein Bicp0 Inhibited the Activation Of Bisg15 Promotementioning
confidence: 93%
“…The viral protein bICP0 which encodes by the immediate early gene of BHV was the candidate protein for repressing expression. The induction of bISG15 in FBL cells treated with poly I:C is mainly stimulated by cellular transactivitor bIRF-3 [14] . 293T cells were co-transfected with a reporter plasmid pGL3-bISG15p, which has a bISG15 promoter at the upstream site of luciferase gene, bIRF-3 expressing plasmid pcDNA-bIRF-3 and bICP0 expressing plasmid pcDNA-bICP0.…”
Section: Bhv Protein Bicp0 Inhibited the Activation Of Bisg15 Promotementioning
confidence: 94%
See 3 more Smart Citations